2019
DOI: 10.1097/aog.0000000000003023
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Analysis of Immigrant Rhetoric on Timely and Regular Access of Prenatal Care

Abstract: Objective. To assess whether recent anti-immigration rhetoric is significantly associated with inadequate prenatal care. Methods. This was a population-based cohort study (2011–2017). In their native language, patients were consented and queried regarding country of origin and time in the United States. Additional variables were collected or abstracted from the medical record, including documentation and timing of prenatal visits. Based on relevance and prevalence during the study period, publicly available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 20 publications
0
37
0
4
Order By: Relevance
“…The medical care of RIs often begins later during pregnancy and is sometimes of lower quality than that of LTRs 4–6 21 23 24. We found this to be even more the case for a subgroup of pregnant women who had been immigrants for less than a year (results in the online supplementary material).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The medical care of RIs often begins later during pregnancy and is sometimes of lower quality than that of LTRs 4–6 21 23 24. We found this to be even more the case for a subgroup of pregnant women who had been immigrants for less than a year (results in the online supplementary material).…”
Section: Discussionmentioning
confidence: 73%
“…This is essentially the consequence of world conflicts and economical concerns 2. It has been reported that immigrants often encounter linguistic, social, political and economic barriers, resulting in reduced access to health systems, and increased morbidity 3–5. Some studies reported a higher prevalence of obstetrical and perinatal complications in immigrant women when compared with native residents 6 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 These examples of problematic communication likely contribute to distrust of medical professionals or the health care system by these ethnicity groups. 16,20 Our analysis of educational background suggested that only the least educated group, those without a high school diploma, were especially skeptical of forceps. This is likely due to lower health literacy.…”
Section: Discussionmentioning
confidence: 90%
“…Regardless of political ideology or one's opinion about ideal immigration policies, there is increasing data indicating that immigration status is associated with health and should be considered a factor in achieving the goal of optimal health for patients and communities. 1 For example, sentiments critical of undocumented immigration and fear of deportation have been associated with changes in health-seeking behaviors 2 and adverse physiological effects. 3 Given this context, health care practitioners and health systems have the opportunity to identify, address, and mitigate the negative consequences that immigration policy and sentiments critical of undocumented immigration may have on the health and well-being of immigrants.…”
mentioning
confidence: 99%